1977
DOI: 10.1021/ac50017a011
|View full text |Cite
|
Sign up to set email alerts
|

Chelex-100 ion-exchange filter membranes for preconcentration in x-ray fluorescence spectrometric analysis of water

Abstract: Fllterlng a 200mL water sample through a palr of Chelex-100 Ion-exchange membranes, under a 2-3 bar pressure, at pH 7 to 8 In not less than 20 mln, leads to an efflclent collection of many trace metals In a form that Is Ideal for subsequent x-ray fluorescence analysls. Slnce enrlchmenl factors around 1250 are obtalned, the detectlon llmlts are at the 1-ppb level. The preclslon Is estlmated to be In the 10-15% range. A perfectly linear relatlonshlp between concentratlon and measured x-ray yleld Is obtalned up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…50 µM ZnSO 4 was added for zinc supplementation studies (ZS). ZA medium was treated with Chelex 100 Beads (Sigma Aldrich) for at least 2 h to chelate bivalent ions [ 57 ] and afterward reconstituted with 500 µM CaCl 2 and 400 µM MgCl 2 to obtain zinc deprived medium (ZD). Zinc concentration in the media was determined by atomic absorption spectroscopy (ZA: 0.176 ± 0.006 mg L −1 ; ZD: 0.024 ± 0.003 mg L −1 ; ZS: 3.633 ± 0.068 mg L −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…50 µM ZnSO 4 was added for zinc supplementation studies (ZS). ZA medium was treated with Chelex 100 Beads (Sigma Aldrich) for at least 2 h to chelate bivalent ions [ 57 ] and afterward reconstituted with 500 µM CaCl 2 and 400 µM MgCl 2 to obtain zinc deprived medium (ZD). Zinc concentration in the media was determined by atomic absorption spectroscopy (ZA: 0.176 ± 0.006 mg L −1 ; ZD: 0.024 ± 0.003 mg L −1 ; ZS: 3.633 ± 0.068 mg L −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that the use of ionexchange resin loaded membranes (or papers) in association with XRF determination is very effective a n d s i m p l e f o r t h e a n a l y s i s o f n a t u ra l w a t e r s (Campbell et al 1966, Blount et al 1973, Van Grieken et al 1977. In contrast, preconcentration procedures for solid materials, which involve the selec tive s e p a ra t i o n o f t ra c e e l e m e n t s a n d q u a n t i t a t i v e deposition on an ion-exchange thin support, need more complex manipulations.…”
Section: Ion Exchange Thin Film Proceduresmentioning
confidence: 99%
“…It shows a good recovery efficiency for a wide range of ions and its chemistry can be predicted from prior experiments with EDTA. The enrichment factors obtained were in excess of 1000, allowing the separation of potassium, calcium, manganese, cobalt, nickel, copper, zinc, rubidium, strontium, and as chlorides or nitrates at element concentrations in the range 10 ppm to 10 ppb [29]. Many other ion exchange resins have also been used.…”
Section: Preconcentration Techniquesmentioning
confidence: 99%